Regions, Power, and Conflict - Thompson, William R. author. aut Link
VIII, 293 p. 93 illus., 9 illus. in color.
Keywords: The three main levels of analysis in international relations have been the systemic, the national, and the individual. A fourth level that falls between the systemic and the national is the region. It is woefully underdeveloped in comparison to the attention afforded the other three. Yet regions tend to be distinctive theaters for international politics. Otherwise, we would not recognize that Middle Eastern interstate politics somehow does not resemble Latin American interstate politics or interstate politics in Southern Africa (although once the Middle East and Southern Africa may have seemed more similar in their mutual fixation with opposition to domestic policies in Israel and South Africa, respectively). This book, divided into three parts, first makes a case for studying regional politics even though it must also be appreciated that regional boundaries are also hazy and not always easy to pin down empirically. The second part examines power distributions within regions as an important entry point to studying regional similarities and differences. Two emphases are stressed. One is that regional power assessments need to be conditioned by controlling for weak states which are more common in some regions than they are in others. The other emphasis is on regional power hierarchies. Some regions have strong regional hierarchies while others do not. Regions with strong hierarchies operate much differently from those without them in the sense that the former are more pacific than the latter. The third part of the book focuses on regional differences in terms of conflict behavior, order preferences, rivalries, and rivalry termination. Co-Authors: William R. Thompson, Thomas J. Volgy, Paul Bezerra, Jacob Cramer, Kelly M. Gordell, Manjeet Pardesi, Karen Rasler, J. Patrick Rhamey, Jr., Kentaro Sakuwa, Rachel D. Van Nostrand, and Leila Zakhirova.